Evaluation of the Relationship between Acromiohumeral Distance and Supraspinatus Tendon Thickness Measured by Ultrasonography and Rotator Cuff Pathologies, Pain, and Function - Dede, B T; Doğan, Y P; Oğuz, M; Bulut, B; Coşkun, H; Aytekin, E (Acta chirurgiae orthopaedicae et traumatologiae Cechoslovaca, 2024)
PURPOSE OF THE STUDY: In this study, we aimed to evaluate acromiohumeral distance (AHD) and supraspinatus tendon (ST) thickness measurements and their relationship with pain and function in ST pathologies. MATERIAL AND METHODS: The study included 111 patients and 25 healthy controls (HC). Patients were divided into 3 groups according to their diagnosis: non-tear tendinopathy (NTT), partial thickness tear (PTT), and full thickness tear (FTT). The AHD and ST thickness of the participants were measured with ultrasound. The pain and functional status of the patients were evaluated with the Numeric Rating Scale (NRS), The QuickDASH shortened version of the DASH Outcome Measure - Disabilities of the Arm Shoulder and Hand (QDASH), and Simple Shoulder Test (SST). RESULTS: The AHD value was significantly higher in the NTT group (p=0.000). The AHD value was significantly lower in the FTT group (p=0.000). ST thickness value was significantly lower in the PTT group compared to the NTT group (p=0.000). There was a positive correlation between ST thickness and BMI (r=0.553,p<0.01). There was a negative correlation between ST thickness and SST and a positive correlation between ST thickness (r=-0.223,p<0.05) and QDASH (r=0.276,p<0.05). CONCLUSIONS: We found that AHD and SST thicknesses significantly differed in the NTT, PTT, FTT, and HC groups. This difference may be important for diagnosis. In addition, the effect of obesity on ST thickness and the relationship between ST thickness and functional scores may be considered. Weight control may be effective at this point. KEY WORDS: acromiohumeral distance, supraspinatus tendon thickness, ultrasound.
Keywords: Male; lidé středního věku; studie případů a kontrol; Acromion; Humans; Middle Aged; rotátorová manžeta; mužské pohlaví; Female; bolest ramene; Tendinopathy; Rotator Cuff; tendinopatie; Case-Control Studies; Pain Measurement; měření bolesti; ženské pohlaví; Ultrasonography; poranění rotátorové manžety; Shoulder Pain; Rotator Cuff Injuries; akromion; Adult; lidé; dospělí; ultrasonografie